Evaluation of kappa carrageenan as potential carrier for floating drug delivery system: Effect of pore forming agents. (1st January 2016) - Selvakumaran, Suguna; Muhamad, Ida Idayu; Abd Razak, Saiful Izwan
Highlights: Preparation of floating kappa carrageenan hydrogels using calcium carbonates and sodium bicarbonates as pore forming agents. The effects of CaCO3 and NaHCO3 on hydrogel characterizations were investigated and compared. CaCO3 produced effective floating hydrogel with excellent structural stability, drug entrapment efficiency and drug release profile than NaHCO3 . CaCO3 was chosen as excellent pore forming agent for effective floating drug delivery system. Abstract: Floating hydrogels were prepared from kappa carrageenan containing CaCO3 and NaHCO3 as pore forming agents. The effects of CaCO3 and NaHCO3 on hydrogel characterizations were investigated and compared. Amoxicillin trihydrate was used as a model drug. Characterizations of the hydrogels were carried out using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and field emission scanning electron microscope (FESEM). As pore forming agents concentration increases, the porosity (%) and floating properties increased. NaHCO3 incorporated hydrogels showed higher porosity with shorter floating lag time (FLT) than CaCO3 . Hydrogel which contained CaCO3 exhibited better gel stability over the control and NaHCO3 containing gel. Incorporation of CaCO3 into kappa carrageenan hydrogel showed smoother surface gels compared to those produced with NaHCO3 . CaCO3 also showed higher drug entrapment efficiency and sustained drug release profile than NaHCO3 . The results of these studies showed that, CaCO3 is an effective pore forming agents in κC hydrogels preparation as compare to NaHCO3 . Thus, CaCO3 can be an excellent pore forming agent for an effective floating drug delivery system.